KULINER DAYOK BINATUR DALAM ADAT ISTIADAT BATAK SIMALUNGUN DI KABUPATEN SIMALUNGUN - Sumbayak, Bosmar Wulan; Hidir, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study examines about Culinary Dayok Binatur in Indigenous Batak Simalungun in Simalungun Regency. Dayok Binatur is a symbol of Simalungun custom food made from chicken meat arranged regularly on the plate. Dayok Binatur is a symbol of traditional food used as an intermediary, to convey a message, advice, or advice delivered from one side of the family to the other family. In this research, examine the meaning of Dayok Bintaur for Batak Simalungun custom and change Dayok Binatur in Batak Simalungun custom. The researchers used the theory of habitus, arena and social capital from Bourdieu. This research method is qualitative descriptive with the number of research subjects 4 people consisting of the oldest traditional figure in Pematang Raya, Sondi Raya. The results of this study indicate that the meaning of Dayok Binatur for the Batak Simalungun custom is to know the function of family life and bermasyarkat in parts of the body of Dayok Binatur. Understand the social capital context of Dayok Binatur, and in Dayok Binatur understand its divisions are called gory. Then change Dayok Binatur in indigenous Batak Simalungun do guidance to young generation to maintain Dayok Binatur as food of Batak Simalungun custom.Keyword: Binoculars Dayok, Meaning, Capital Sikik